EL DEVENIR MINORITARIO COMO CLAVE DE LECTURA EN LAS POÉTICAS NEOBAROCAS DE NÉSTOR PERLONGHER Y ANTONIO SILVA. - Hernández O., Biviana (Revista Chilena de Literatura)
In this article I propose a neo-baroque key reading of Néstor Perlongher's and Antonio Silva's poetics. I mean a writing of sexual, political and sublime violence to which the body, as an anatomic fiction, is subjected to. For this purpose, I will exploit the notion of "minoritary becoming" as the otherness's critical verbalization space; and as such, as a territorial and political boundary from where is possible to question Power's aesthetical-symbolic limits and hegemonic discourses of control over the bodies and sexualities.